First record of Miltogramminae from New Caledonia: a new species of Protomiltogramma (Diptera: Sarcophagidae) - Johnston, Nikolas P.; Wallman, James F.; Pape, Thomas (Zootaxa, 2019)
New Caledonia is described as one of Earth’s key biodiversity hotspots, with high species endemism, particularly for plants and vertebrate animals (Myers et al. 2000; Kier et al. 2009). The distinct biodiversity of this country has been attributed to the Gondwanan origins of the New Caledonian archipelago, its relative isolation from neighbouring countries (such as Australia) and the stability of its climate. These factors are suggested to have led to the accumulation of many Gondwanan species, with few instances of extinction, which has allowed for marked species diversification (Espeland & Murienne 2011).